Utilização de sorgo grão inteiro e moído em dietas de frangos de corte - Fagundes, Cleber (2014)
The aim of this experiment was to evaluate the growth performance, yield cuts, carcass composition and metabolizable energy intake, lysine and methionine + cystine in male broiler chickens, 21 days to 42 days, with different diets based on sorghum grain, ground grain sorghum and corn. 112 Cobb 500 strain of birds divided into 28 cages with four birds per cage were used in a completely randomized design with four treatments and seven repetitions: control group (T1) containing: a diet based on ground corn and soybean meal ; Treatment 2 (T2) with a diet based on ground sorghum and soybean meal; Treatment 3 (T3) with ground sorghum grain and soybean meal and treatment 4 (T4) with T3 in separate feed troughs in fraction (a): sorghum grain fraction and (b) concentrate containing the other feed ingredients properly mixed system (libre choice). Were studied, feed intake (FI); Body weight (BW); feed conversion rate (FCR); Viability (V); breast yield (BY); thigh (T) and drumstick (D); chemical composition of pectoris (CP) and thigh with drumstick (TD); daily intakes of metabolizable energy (ME), lysine (L) and methionine + cystine (MC). These variables were subjected to analysis of variance (ANOVA) and treatment means compared to each other by the Scott-Knott test (P <0.05). We conclude that the use of sorghum grain in diets is feasible and contributes to reduce manufacturing and logistics costs in the poultry industry and promotes the same results of growth performance, yield and chemical composition of cuts compared to diets with corn and sorghum ground. The strategy of feeding the birds in the free choice system with sorghum whole grain separated and concentrated at the feeder in the period 21-42 days of age, demonstrates a high degree of capacity for self regulation of poultry intake of energy and protein.